Tinjauan Aspek Sosial Budaya Dalam Merokok Elektronik Di Kalangan Remaja - Ridwan, Muhammad (JUKEJ : Jurnal Kesehatan Jompa, 2025)
AbstractElectronic cigarettes are a modern innovation as an alternative to tobacco tobacco which is widely used among adolescents and active smokers. This study aims to explore in depth the socio-cultural aspects that underlie and influence electronic smoking (vaping) behavior among adolescents. The methods used are qualitative, literature review studies, journals, the internet, and previous research. Initial findings indicate that the use of electronic cigarettes among adolescents is not only influenced by nicotine addiction factors, but also by peer group dynamics, the desire to be accepted and recognized, and the construction of self-identity. Social media and lifestyle trends also play an important role in shaping perceptions and normalization of vaping in the adolescent environment. This study highlights the importance of considering the socio-cultural context in prevention and intervention efforts related to the use of electronic cigarettes among adolescents. The implications of this study are expected to provide more comprehensive insights for public health policy research and prevention programs that are more effective and relevant to the socio-cultural realities of adolescents. Keywords: Electronic Cigarettes, Socio-Culture, Adolescents.